Neuroprotective effects and mechanisms of osteocalcin in an Alzheimer’s disease cell model - FANG Lilin; FANG Lilin; ZHU Qifeng; ZHU Qifeng; ZHANG Mingda (陆军军医大学学报)
Objective‍　‍To explore the neuroprotective effects of osteocalcin (OCN) on an Alzheimer’s disease (AD) cell model and its potential mechanisms, providing a scientific basis for new therapeutic targets for AD. Methods‍　‍Human neuroblastoma cell line SH-SY5Y was treated with 40 nmol/L okadaic acid (OA) for 24 h to establish an AD cell model. The cells were divided into a normal group (untreated SH-SY5Y cells), a model group (40 nmol/L OA intervention), and an OCN intervention group (intervention with various concentrations of OCN in the AD cell model), and AKT knockout/overexpression groups( AKT-KO group and AKT-OE group), and AKT-KO OCN group and AKT-OE OCN group. CCK-8 assay was used to detect the changes in cell viability. Wright's staining was employed to observe the morphological changes of AD cells. Western blotting was utilized to detect the protein levels of Tau, p-Tau, Bax, Bcl-2, Caspase-3 and their lytic types, as well as the expression of Tau, p-Tau, mTOR, AKT and p-AKT in each group after AKT knockout/overexpression. TUNEL staining and flow cytometry were applied to detect the changes in early and late apoptotic cells and the apoptotic rate in the OCN-treated AD cell model. Results‍　‍①Compared to the normal group, the model group exhibited a significant decrease in cell viability, noticeable morphological and structural damage, upregulation of p-Tau and Caspase-3, increased early and late apoptosis, and a significantly higher apoptotic rate (P<0.05). ②After treatment of different concentrations of OCN for 24 h, cell viability was increased to varying degrees compared to the AD model group, with the 100 pg/mL OCN group showing a significant increase in cell viability (P<0.01) and marked improvement in cell number and morphology (P<0.01). ③ Compared to the AD cell model group, the p-Tau/Tau ratio was decreased in all OCN treatment groups, particularly in the 100 pg/mL OCN intervention group, where the p-Tau/Tau ratio was significantly lower than that of the model group (P<0.01). ④ Compared to the model group, a significant concentration-dependent decrease in the Cleaved Caspase-3/Caspase-3 ratio was observed when OCN concentrations ranged from 1 to 100 pg/mL, with a significant reduction in the Bax/Bcl-2 ratio in the 100 pg/mL group (P<0.000 1). ⑤ The results of TUNEL staining and flow cytometry showed that, compared to the model group, all concentrations of OCN effectively inhibited the apoptosis in the AD model cells, with a significant reduction in early and late apoptotic cells and apoptotic rate in the 100 pg/mL OCN group. ⑥ Compared with the control group and the model group, the P-AKT was significantly increased in the AKT-OE group after AKT overexpression (P<0.05). The expression level of AKT protein was decreased in the AKT-KO group after AKT knockout (P<0.05). When the AKT pathway was inhibited, the expression level of p-Tau was higher in the AKT-KO group than the control group (P<0.05), and when the AKT was overexpressed, the expression level was significantly inhibited (P<0.05). Conclusion‍　‍OCN may inhibit cell apoptosis and reduce p-tau protein level by regulating the ratio of Caspase-3/Caspase-3 and Bax/Bcl-2, and thereby improve the morphology of AD model cells and effectively protect nerve cells, which may be related to the regulation of the AKT/mTOR pathway.